2010
DOI: 10.3802/jgo.2010.21.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Maximal cytoreductive effort in epithelial ovarian cancer surgery

Abstract: The surgical management of advanced epithelial ovarian cancer involves cytoreduction, or removal of grossly-evident tumor. Residual disease after surgical cytoreduction of ovarian cancer has been shown to be strongly associated with survival. The goal of surgery is "optimal" surgical cytoreduction, which is generally defined as residual disease of 1 cm or less. However, the designation of "optimal" surgical cytoreduction has evolved to include maximal surgical effort and no gross residual disease. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
90
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 59 publications
3
90
1
2
Order By: Relevance
“…На вероятность возникновения рецидива заболева-ния влияет интраоперационное выявление макроскопи-ческих изменений: прорастание опухоли в капсулу кисто-мы или наличие опухолевых клеток в асците, нарушение целостности капсулы опухоли при хирургических мани-пуляциях, массивные сращения и спайки опухоли с окру-жающими тканями [8,9].…”
unclassified
“…На вероятность возникновения рецидива заболева-ния влияет интраоперационное выявление макроскопи-ческих изменений: прорастание опухоли в капсулу кисто-мы или наличие опухолевых клеток в асците, нарушение целостности капсулы опухоли при хирургических мани-пуляциях, массивные сращения и спайки опухоли с окру-жающими тканями [8,9].…”
unclassified
“…A number of studies have consistently shown that optimal cytoreduction is associated with a significant survival benefit in patients with this disease [8,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that residual disease (RD) after initial surgery is a strong independent prognostic factor for survival and recurrence, with improvements in both overall and progression free survival being greatest in women with no (currently termed complete cytoreduction) or minimal (<1 cm, currently termed optimal cytoreduction) visible residual disease post-operatively [4][5][6][12][13][14]. A number of studies have consistently shown that optimal cytoreduction is associated with a significant survival benefit in patients with this disease [8,11,14].…”
Section: Introductionmentioning
confidence: 99%
“…A majority of women will have advanced-stage disease at initial diagnosis, and this is intimately linked to poor prognosis of the disease. The International Federation of Gynecology and Obstetrics (FIGO) classification of the disease stage is the strongest predicting factor of survival [3] . Patients with advanced-stage disease will experience relapse and only 20%-25% of patients can be expected to be long-term survivors despite showing a good response to primary treatment [4] .…”
Section: Introductionmentioning
confidence: 99%